Overweight and obese humans demonstrate increased vascular endothelial NAD(P)H oxidase-p47(phox) expression and evidence of endothelial oxidative stress - Silver, Annemarie E; Beske, Stacy D; Christou, Demetra D; Donato, Anthony J; Moreau, Kerrie L; Eskurza, Iratxe; Gates, Phillip E; Seals, Douglas R (Circulation (New York, N.Y.), 2007)
Obesity may alter vascular endothelial cell protein expression (VECPE) of molecules that influence susceptibility to atherosclerosis. Quantitative immunofluorescence was performed on vascular endothelial cells collected from 108 men and women free of clinical disease who varied widely in adiposity (body mass index 18.4 to 36.7 kg/m2; total body fat 5.8 to 55.0 kg; waist circumference: 63.0 to 122.9 cm). All 3 expressions of adiposity were positively associated with VECPE of the oxidant enzyme subunit NAD(P)H oxidase-p47(phox) (part correlation coefficient [r(part)] 0.22 to 0.24, all P < 0.05) and the antioxidant enzyme catalase (r(part) = 0.71 to 0.75, all P < 0.001). Total body fat was positively associated with VECPE of nitrotyrosine (r(part) = 0.36, P = 0.003), a marker of protein oxidation, and, in men, with Ser1177-phosphorylated endothelial nitric oxide synthase (r(part) = 0.46, P = 0.02), an activated form of endothelial nitric oxide synthase. Overweight/obese subjects (body mass index > or = 25 kg/m2) had 35% to 130% higher VECPE of NAD(P)H oxidase-p47(phox), nitrotyrosine, catalase, and the cytosolic antioxidant CuZn superoxide dismutase (all P < 0.05), as well as a 56% greater VECPE of the potent local vasoconstrictor endothelin-1 (P = 0.05) than normal-weight subjects (body mass index < 25 kg/m2). Nuclear factor-kappaB protein expression was approximately 60% to 100% greater in the most obese adults than in the leanest adults (P < or = 0.01). These relations were independent of sex but were selectively reduced after accounting for the influence of plasma C-reactive protein, fasting glucose-insulin metabolism, or serum triglycerides. Compared with their normal-weight peers, overweight and obese adults demonstrate increased vascular endothelial expression of NAD(P)H oxidase-p47(phox) and evidence of endothelial oxidative stress, with selective compensatory upregulation of antioxidant enzymes and Ser1177-phosphorylated endothelial nitric oxide synthase. Endothelin-1 and nuclear factor-kappaB protein expression also appear to be elevated in obese compared with lean adults. These findings may provide novel insight into the molecular mechanisms linking obesity to increased risk of clinical atherosclerotic diseases in humans.